Anti-hyperammonaemic effect of fisetin in rats: A chronotherapeutic study - Murugesan Jayakumar; Onn Haji Hashim; Perumal Subramanian (International Journal of Phytomedicine, 2014)
Ammonia, a product of degradation of proteins and other nitrogen compounds is toxic at higher concentrations. Fisetin (a naturally occurring flavonoid) is known to exhibit a number of cytoprotective effects. In this study, chronotherapeutic effects of fisetin on ammonium chloride (AC) treated rats is aimed to establish the time point at which the maximum drug effect is achieved. Fisetin (50 mg/kg b.w oral) was administrated to rats at 06:00, 12:00, 18:00 and 00:00 h against AC (100 mg/kg.b.w. i.p) treated Wistar rats (180-200 g). Amelioration of pathophysiology of AC induced hyperammonaemic characteristics by fisetin at different time points were measured by assessing cellular architecture of liver and brain, lipid profile, lipid peroxidation products and antioxidants (superoxide dismutase, catalase, glutathione peroxidase and reduced glutathione) in serum, plasma, liver and brain. The normalization of lipid profile and markers of reactive oxygen species (ROS) homeostasis indicated the protective effect of fisetin. Fisetin administration at 00:00 h showed significant effects on these indices than at other time points (p<0.05; DMRT). This might be due to chronopharmacokinetic and chronopharmacodynamic properties of fisetin along with its action on altered rhythms of lipid profile and markers of ROS homeostasis.